490 mA/mm drain current and 1.9 V threshold voltage enhancement-mode p-GaN HEMTs and high-temperature characteristics. (December 2021) - Liu, Kai; Wang, Chong; Zheng, Xuefeng; Ma, Xiaohua; Huang, Zeyang; He, Yunlong; Li, Ang; Zhao, Yaopeng; Mao, Wei; Hao, Yue
Highlights: Achieving high drain current of the p-GaN HEMTs. Maintaining a relatively high threshold voltage. Improving the characteristics of devices by the post gate annealing treatment. High-temperature characteristic analysis. Abstract: In this paper, enhancement-mode AlGaN/GaN p-type GaN cap layer high electron mobility transistors (p-GaN HEMTs) with Ti/Au gate metal are fabricated and electrically characterized. The post gate annealing (PGA) treatment at 300 °C for 10 min is utilized to improve the devices' characteristics. As a result, the p-GaN HEMTs achieve a high drain current ( IDS ) of 490 mA/mm at VGS = 7 V with a high threshold voltage ( VTH ) of 1.9 V. Meanwhile, the pulse measurements show good dynamic characteristics, and the temperature-dependent characteristics indicate that the VTH has excellent high-temperature stability from 25 °C to 175 °C. Besides, it can be found that the temperature will affect the capacitance–voltage ( C-V ) and transconductance curves, which is related to the hole energy and electron mobility at different temperatures.